Erasmus Exchange Program - A Matter of (Relatively) Older Students - M. Carlsson; L. Fumarco; B. G. Gibbs (Global Labor Organization (GLO), 2020)
This study contributes to the literature on long-term effects of relative age (i.e. age differences between classmates in compulsory school) by examining tertiary education outcomes. We investigate whether there is evidence of relative age effects on university students enrolled in the Erasmus exchange program. We use administrative data on all exchange students who visited the Linnaeus University, in Sweden, in the four years since its founding. We find long-term evidence of RAEs—the youngest cohort students participate less often to the Erasmus exchange program than older cohort members.
Keywords: D04; I21; I23; I24; 330; Educational Policy; Higher Education; International Education/Studies; Migration; Policy Analysis